Transportation of Spent Nuclear Fuel ([s.n.], 1998)
Provides background on transportation of spent nuclear fuel and discusses adequacy of Nuclear Regulatory Commission standards for shipping casks, probabilities and potential consequences of transportation accidents, and possible routes for nuclear waste shipments.
Record is based on bibliographic data in ProQuest U.S. Congressional Research Digital Collection (last viewed July 2010). Reuse except for individual research requires license from ProQuest, LLC.
CRS Report.
Keywords: Radioactive substances.; Sabotage.; Transportation accidents.